Specialist healthcare services for concussion/mild traumatic brain injury in England: a consensus statement using modified Delphi methodology - Antonio Belli; Vanessa Raymont; Damian Holliman; Catherine McMahon; Peter Whitfield; Mark Wilson; Angelos G Kolias; Ben Jones; Richard Sylvester; Mario Ganau; Michael Parker; Shrouk Messahel; et al. (BMJ Open)
Objective To establish a consensus on the structure and process of healthcare services for patients with concussion in England to facilitate better healthcare quality and patient outcome.Design This consensus study followed the modified Delphi methodology with five phases: participant identification, item development, two rounds of voting and a meeting to finalise the consensus statements. The predefined threshold for agreement was set at ≥70%.Setting Specialist outpatient services.Participants Members of the UK Head Injury Network were invited to participate. The network consists of clinical specialists in head injury practising in emergency medicine, neurology, neuropsychology, neurosurgery, paediatric medicine, rehabilitation medicine and sports and exercise medicine in England.Primary outcome measure A consensus statement on the structure and process of specialist outpatient care for patients with concussion in England.Results 55 items were voted on in the first round. 29 items were removed following the first voting round and 3 items were removed following the second voting round. Items were modified where appropriate. A final 18 statements reached consensus covering 3 main topics in specialist healthcare services for concussion; care pathway to structured follow-up, prognosis and measures of recovery, and provision of outpatient clinics.Conclusions This work presents statements on how the healthcare services for patients with concussion in England could be redesigned to meet their health needs. Future work will seek to implement these into the clinical pathway.